Topics in Fluorescence Spectroscopy : Volume 6: Protein Fluorescence - Lakowicz, Joseph R. (Topics in fluorescence spectroscopy, 2002)
This sixth volume in the highly regarded series is an essential addition to libraries serving analytical chemists, spectroscopists, biochemists, and biophysicists. Maintaining the high standards set by its predecessors, Protein Fluorescence presents twelve state-of-the-art chapters by some of the most respected researchers in the field.